Nesting ecology of Spectacled Eiders Somateria fischeri on the Indigirka River Delta, Russia - Pearce, John M; Esler, Daniel; Degtyarev, Andrei G (Wildfowl, 1998)
In 1994 and 1995 we investigated breeding biology and nest site habitat of Spectacled Eiders on two study areas within the coastal fringe of the Indigirka River Delta, Russia (71 degrees 20' N, 150 degrees 20' E). Spectacled Eiders were first observed on 6 June in both years and nesting commenced by mid-June. Average clutch size declined with later nest initiation dates by 0.10 eggs per day; clutches were larger in 1994 than 1995 and were slightly larger on a coastal island study area compared to an interior area. Nesting success varied substantially between years, with estimates of 1.6% in 1994 and 27.6% in 1995. Total egg loss, through avian or mammalian predation, occurred more frequently than partial egg loss. Partial egg loss was detected in 16 nests and appeared unrelated to nest initiation date or clutch size. We found no difference among survival rates of nests visited weekly, biweekly, and those at which the hen was never flushed, suggesting that researcher presence did not adversely affect nesting success. A comparison of nine habitat variables within each study area revealed little difference between nest sites and a comparable number of randomly located sites, leading us to conclude that Spectacled Eiders nest randomly with respect to most small scale habitat features. We propose that large scale landscape features are more important indicators of nesting habitat as they may afford greater protection from land-based predators, such as the Arctic Fox. Demographic data collected during this study, along with recent conservation measures implemented by the Republic of Sakha (Yakutia), lead us to conclude that there are few threats to the Indigirka River Delta Spectacled Eider population. Presently, the Indigirka River Delta contains the largest concentration of nesting Spectacled Eiders and deserves continued monitoring and conservation.